Description of Ossinissa, a new pholcid genus from the Canary Islands (Araneae: Pholcidae) - Dimitrov, Dimitar; Ribera, Carles (Zootaxa, 2005)
Ossinissa new genus (Araneae, Pholcidae) is described to place a Canarian pholcid species formerly considered belonging to Spermophorides. The male of the type species, Ossinissa justoi (Wunderlich) new combination, is described for the first time and the female is re-described. This new genus is supported by a revision of the morphological characters of the female, the newly discovered male, and a cladistic analysis.